Association between the COMT Val158Met polymorphism and fibromyalgia susceptibility and fibromyalgia impact questionnaire score: a meta-analysis - Lee, Young Ho; Kim, Jae-Hoon; Song, Gwan Gyu (Rheumatology international, 2015)
The aim of this study was to explore whether the catechol- O -methyltransferase (COMT) Val158Met polymorphism is associated with susceptibility to fibromyalgia and fibromyalgia impact questionnaire (FIQ) score in fibromyalgia patients. We conducted a meta-analysis of the associations of the COMT Val158Met polymorphism with fibromyalgia risk as well as FIQ score in fibromyalgia patients. A total of 993 fibromyalgia patients and 778 controls from 10 studies on the COMT Val158Met polymorphism and 538 fibromyalgia patients from 5 studies on the COMT Val158Met polymorphism and FIQ score were included in this meta-analysis. The meta-analysis revealed an association between fibromyalgia and the COMT Met/Met + Val/Met genotype in all study subjects (odds ratio (OR) 1.635, 95 % confidence interval (CI) 1.029–2.597, p = 0.037). However, stratification by ethnicity indicated no association between the Met/Met + Val/Met genotype and fibromyalgia in the European and Turkish populations (OR 1.202, 95 % CI 0.876–1.649, p = 0.255; OR 2.132, 95 % CI 0.764–5.949, p = 0.148, respectively). Analysis using other genetic models showed no association between the COMT Val158Met polymorphism and fibromyalgia. The meta-analysis also revealed that the FIQ score was significantly higher in individuals with the COMT Met/Met genotype than in those with the Val/Val genotype [weighted mean difference (WMD) = 14.39, 95 % CI 3.316–25.48, p = 0.011] and the Val/Met genotype (WMD = 5.108, 95 % CI 2.212–4.891, p = 0.021). This meta-analysis identified an association between fibromyalgia risk and the COMT Val158Met polymorphism as well as the FIQ score in fibromyalgia patients.